Trends in all-cause mortality of atrial fibrillation in hospitalized patients in Sweden between 1995–2008. (14th October 2021) - Sztaniszlav, A; Magnuson, A; Bryngelsson, I L; Edvardsson, N; Sztaniszlav, K; Poci, D
Abstract: Introduction: Atrial fibrillation (AF) is the most common arrythmia. Both its incidence and prevalence increased significantly during the last decades. AF is associated with high morbidity and mortality. Purpose: The aim of this study was to describe and evaluate the trends of all-cause mortality in patients first-ever hospitalized for AF, and the effect of age, sex, stroke risk, and education level on mortality over time. Methods: In this observational retrospective cohort study, we enrolled the patients who were hospitalized primarily and for the first time because of AF between 1st January 1995 and 31st December 2004. In regard to the date of the index admission patients were divided into four cohorts and they were followed up to five years. Patients were compared with an age and sex matched control population. All data were collected from Swedish national registries. Kaplan-Meier plots and Cox regression with trend analysis were used for statistical evaluation. Results: In total 64 489 AF patients (mean age 72±10.1 year) were included in this study. The control group comprised 116 893 individuals. 81.9% of the women and 58.5% of the men were older than 65 years of age. 65.5% of women and 58.5% of the men had a stroke risk of CHADS2-VA2Sc ≥2. We found a significantly decreasing trend of the relative risk for all-cause mortality in AF patients over time: trend HR: 0.94 (95% CI: 0.92–0.96, p<0.001) in women and trend HR: 0.91 (95% CI: 0.89–0.93 p<0.001) in men. The mortality trends between AF patients and their controls did not show significant difference: trend HR: 0.99 (95% CI: 0.96–1.02, p=0.59) in women and trend HR: 1.00 (95% CI: 0.97–1.03, p=0.98) in men. The subpopulation analysis showed that the mortality risk remained unchanged over the time in women aged 18–69 years (trend HR: 0.91 – 95% CI: 0.82–1.02, p=0.099), in patients with low stroke risk (trend HR: 1.08 – 95% CI: 0.92–1.26, p=0.36 in women and trend HR: 0.95 – 95% CI: 0.87–1.05, p=0.30 in men) and in patients with post-secondary level of education (trend HR: 0.93 – 95% CI 0.83–1.04, p=0.23 in women and trend HR: 1.04 – 95% CI: 0.96–1.12, p=0.32 in men). Conclusion: The all-cause mortality risk of the AF hospitalized patients was higher compared to control population and had a decreasing tendency during the time of the study. However, this trend is not significantly different from the control population. We found unchanged mortality trend in younger patients, in those with lower stroke risk, and in patients with higher education level. Funding Acknowledgement: Type of funding sources: None.